SOCIO‑ECONOMIC ANALYSIS OF THE STRUCTURE AND DEVELOPMENT POTENTIAL OF TERRITORIAL COMMUNITIES OF EASTERN PODILLIA - Shvets, Oleksandr; Mudrak, Oleksandr (Public Management and Policy, 2025)
This article presents a comprehensive study of the socio-economic structure and development potential of territorial communities in Eastern Podillia, in the context of the decentralization reform in Ukraine. The relevance of the topic stems from the need for an in-depth analysis of community structures as basic local self-government units, considering their resource capacity, institutional strength, and spatial characteristics, which directly affect regional policy and management effectiveness. The main goal of the study is to perform a socio-economic analysis of the territorial communities in Eastern Podillia, taking into account their structural differentiation and development dynamics. The object of the research is the territorial communities as spatial-administrative entities, while the subject is their structure, development level, and internal potential. The geographical scope includes the southern part of Khmelnytskyi region, the central and northern parts of Vinnytsia region, and part of Cherkasy region. The article applies a range of methods, including index, cluster, and correlation-regression analysis, expert evaluation, and GIS-based visualization approaches. Based on the calculated indicators, the communities were classified into three development levels: high, medium, and low. Specific examples of communities with different development statuses are given, such as Zhmerynka, Kalynivka, and Severynivka. The study identifies key factors that shape the development potential of communities: financial capacity, local economic structure, human capital, infrastructure, and governance quality. The findings reveal regional development disparities and serve as a basis for practical recommendations in strategic community planning based on development potential. The scientific novelty of the work lies in the integrated analytical approach to studying communities of Eastern Podillia, combining quantitative indicators with spatial characteristics. The practical value is in the applicability of results for local governments, regional authorities, and developers of territorial development strategies.